Pengaruh Kredibilitas Komunikasi Penyuluh Lapangan Keluarga Berencana (PLKB) Terhadap Peningkatan Akseptor Keluarga Berencana Di Kota Medan - Viana Safrida Harahap (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
The research objective  for  analyze the effect of communication credibility of Field Extension Officer for Family Planning (PLKB) towards the Increasing of family planning acceptors in Medan. Analyze credibility communication of Field Extension Officer for Family Planning (PLKB) in Medan. Analyze the increasing of Family Planning acceptor in Medan. Researcher using the paradigm of positivism as a research guideline, which is researcher defined as a process of the linear communication or causal process that reflects the communicator to alter the knowledge (attitudes or behavior) of the passive communicant.  The results of the research are the communication credibility of PLKB towards the increasing of family planning acceptors in Medan has a positive and significant relation. Corellation value of Karl Spearman by 0,59 have correlation two variable can be stated there are effect of the communication credibility of PLKB towards the increasing of family planning acceptors in Medan.  The communication credibility of PLKB in Medan based on the standart honesty, the professionalism, the dynamic and the objective in counselling to execution of duties everyday. Increasing of family planning acceptors in Medan achieved by organizing, implementing, monitoring and evaluation of program KB  on the claim, warrants, and data.